Literature Review : Hubungan Status Gizi dengan Tuberkulosis Paru - Fetty Imanda; Indra Buana (Lembaga Pengembangan Kinerja Dosen, 2026)
Tuberculosis (TB) remains a major global health problem with high morbidity and mortality rates, particularly in high-burden countries such as Indonesia. Nutritional status is one of the important factors influencing the incidence and outcomes of TB. This literature review aims to analyze the relationship between nutritional status and pulmonary tuberculosis based on recent national and international studies. Articles were retrieved from Google Scholar, PubMed, and Portal Garuda using the keywords “nutritional status” and “tuberculosis” as well as “status gizi tuberculosis” within the period of 2019–2024. Eligible articles were analyzed descriptively. The findings indicate that poor nutritional status is significantly associated with an increased risk of pulmonary tuberculosis. Malnutrition impairs cellular immunity, particularly T-lymphocyte and macrophage function, thereby increasing susceptibility to Mycobacterium tuberculosis infection. Conversely, active TB infection can worsen nutritional status through increased energy expenditure, decreased appetite, and metabolic alterations. This bidirectional relationship highlights the crucial role of nutritional interventions in TB prevention and management. Therefore, improving nutritional status should be considered an integral component of tuberculosis control strategies.